PENGARUH HARGA DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PERUMAHAN PERSADA BANTEN PADA PT. HARAPAN INTI PERSADA DI KOTA SERANG - Surti Zahra; Nita Nurindah Sari; Tb. Agus Khoironi (National Conference on Applied Business, Education, & Technology (NCABET), 2022)
This study was structured using quantitative methods. The population in this study were 3,370 respondents who were consumers who had purchased housing Persada Banten. The sample in this study was 97 respondents using the non-pribability sampling technique, namely the accidental sampling technique. The results of this study indicate that the indicators are valid and reliable, the significance level of this study is 5%. In the classical assumption test, the regression model was found to be normally distributed, free of heteroscedasticity and free of multicollinearity. The results of the analysis show that partially the price has no effect on purchasing decisions and brand image has an effect on purchasing decisions. Then the price and brand image simultaneously have a positive and significant influence on purchasing decisions